Gambaran Balance Cairan Pada Anak Diare Setelah Diberikan Pemenuhan Kebutuhan Cairan di Rumah Sakit Kaliwates Jember - Prasetyo Adi Prabowo; Lantin Sulistyorini; Peni Perdani Juliningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
Diarrhea is a global event in various countries, including in many developing countries. Management of diarrhea is to use fluid rehydration. Other diarrhea management can be used with supplements, using Oral Rehydration Salt (ORS), using medication from the doctor, and drinking lots of water to replace lost fluids. This study aims to determine how to describe the fluid balance in children with diarrhea after being given the fulfillment of fluid needs in the hospital. The research was conducted at Kaliwates Hospital in Jember, with the research time used by researchers was one month. The sample of this study was thirty-two children of diarrhea patients with mild, moderate, severe dehydration. Data collection was carried out for three days while the child is hospitalized. The result of this study was obtained from total sampling. It was obtained that the fluid balance in diarrhea children did not all turn into balance. There was excess fluid, and they still experienced dehydration. From the research data, it was found that most of the experience of extra fluid status. The study concludes that after rehydration, children have an increasing fluid status. Fulfillment of fluids in children with diarrhea aims to reduce the risk of decreased fluid and maintain body fluids when they lose fluid through liquid feces. Fluid balance makes people's body became immune to the disease.